Prospects and Challenges of Implementation Citizens Charter (Inovation of Public Services at the Community Health Center Jayapura District) - Hadiyanto, Soemedi (Universitas Cenderawasih, 2015)
Introduction : Citizens Charter indicates the rights and services available to the public, service procedures, forms available services and community obligations that must be met (Haque, 2005). Objective : This paper seeks to examine the prospects and challenges of implementation of Citizens Charter as a public service innovation in Jayapura subdistrict health center. Method of approach : the scope of this paper started in 2000 until today, especially with regard to the implementation of public service experience of the health sector and implementation of Citizens Charter in Indonesia and based on secondary sources of information, and using a combination of descriptive and analytical methods. Study Results : This paper shows that despite the bureaucratic reform, especially public services have stepped into the right direction, the impact has so far been less than expected. Despite some reforms and improvements they have made in the provision of services, the public continues to suffer from bureaucratic inefficiency, corruption and a host of other problems, so it shows the gap between the rhetoric and reality of public management reform in Indonesia. It is expected to be the opportunities and challenges for scholars interested in public management (Citizens Charter)-either in academics or policy makers, especially in the implementation in Jayapura . Conclusions : Implementation of the Citizens Charter will efficiently and effectively if attention to some factors : campaigns and dissemination of all stakeholders should be designed and carried out innovative, effective and sustainable to obtain a change of attitude and cultural wisdom ; involve staff in each formulation and implementation ; must have a mechanism structured on monitoringand evaluation, and preferably through an independent agent. Keywords : implementation of Citizens Charter, health centers, innovation, prospects and challenges.